Intentional Replantation of Molar Tooth A Case Report of 14 Years old Girl (City Dental College Journal, 2012)
A case of extensively decayed of right lower 1st molar tooth with a filling was extracted first and then it was treated by root canal filling outside of the mouth and reinserted into the socket and immobilized by inter-dental wiring in October, 1992. It had been reported in 2006 that the treated tooth was healthy without any complaint of patient. The success of intentional replantation procedure appears to be better in younger age.DOI: http://dx.doi.org/10.3329/cdcj.v9i1.11836 City Dental College Journal Vol.9(1) 2012 32-34